Performance and competitive displacement of Bemisia tabaci MEAM1 and MED cryptic species on different host plants - Watanabe, Luís Fernando Maranho [UNESP]; Bello, Vinicius Henrique [UNESP]; De Marchi, Bruno Rossitto [UNESP]; Silva, Felipe Barreto da [UNESP]; Fusco, Lucas Machado [UNESP]; Sartori, Maria MárciaPereira [UNESP]; Pavan, Marcelo Agenor [UNESP]; Krause-Sakate, Renate [UNESP] (Elsevier, 2019)
Bemisia tabaci comprises a complex of cryptic species, of which MEAM1 (known as B biotype) and MED (known as Q biotype) are the most invasive and widely distributed ones. In Brazil, MEAM1 was first reported in the 1990s, while MED was first reported in 2014. The goal of this study was to understand the behaviour of the newly introduced MED cryptic species in Brazil and to predict the susceptibility of soybean, cotton, common bean, tomato and sweet pepper to it in the absence of insecticides. We investigated the performance as well as the competitive displacement of these cryptic species in the selected hosts. The best performance of MED was observed on common bean, followed by sweet pepper, propitiating the emergence of a large number of adults and a higher survival rate (±60 and 50% for MED, respectively, while for MEAM1, 20% was reached). In addition, MED displaced MEAM1 in sweet pepper and common bean after four generations (after 120 days, all insects were 100% MED). By contrast, MEAM1 displaced MED only in tomato after four generations. The competitive displacement and the performance results were the same, indicating the most suitable host for each species. Both MED and MEAM1 are well adapted to cotton and soybean plants, and no advantage was observed for one particular species in the absence of insecticides. Common bean and sweet pepper are excellent hosts for B. tabaci MED cryptic species, requiring increased attention by the producer. The year-round common bean cultivation in Brazil could contribute to the adaptation of MED to open field production in Brazil and, consequently, to the migration to other crops such as soybean and cotton, to which MED is also well adapted. Further management studies with these cryptic species in Brazil, including insecticide experiments and biological control assays, are necessary.
Keywords: Common bean; Cotton; Soybean; Sweet pepper; Tomato; Whitefly